2009
DOI: 10.1521/suli.2009.39.6.599
|View full text |Cite
|
Sign up to set email alerts
|

Thoughts of Death and Suicide in Early Adolescence

Abstract: This community-based study estimates the prevalence and persistence of thoughts of death and suicide during early adolescence. A latent class approach was used to identify distinct subgroups based on endorsements to depression items administered repeatedly over 24 months. Two classes emerged, with 75% in a LOW IDEATION class across four assessments. <2% persisted in the HIGH IDEATION class over 3+ assessments. African American and Asian American adolescents were more likely than European Americans to belong to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
34
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 38 publications
6
34
1
Order By: Relevance
“…More specifically, this study’s finding that members of one higher risk class (class 5) reported fewer depressive symptoms than a lower risk class (class 4) is consistent with two studies of suicide decedents that found at least one class without depressive symptoms, and with a prospective study where the high risk group had fewer depressed members than the medium risk group (Judd et al, 2012; Logan et al, 2011; Thompson et al, 2009). These results are in contrast to one large cohort study that identified only two latent classes, which they termed low versus high ideation, and a smaller study of suicide decedents that found depressive symptoms were distributed across all the latent classes, with childhood onset, co-morbidity, and substance misuse predicting class membership (Kim et al, 2003; Stoep et al, 2009). …”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…More specifically, this study’s finding that members of one higher risk class (class 5) reported fewer depressive symptoms than a lower risk class (class 4) is consistent with two studies of suicide decedents that found at least one class without depressive symptoms, and with a prospective study where the high risk group had fewer depressed members than the medium risk group (Judd et al, 2012; Logan et al, 2011; Thompson et al, 2009). These results are in contrast to one large cohort study that identified only two latent classes, which they termed low versus high ideation, and a smaller study of suicide decedents that found depressive symptoms were distributed across all the latent classes, with childhood onset, co-morbidity, and substance misuse predicting class membership (Kim et al, 2003; Stoep et al, 2009). …”
Section: Discussioncontrasting
confidence: 99%
“…In the suicide risk literature, LCA has been used to identify precipitants for suicidal thoughts among adolescents of various ethnic and racial backgrounds (De Luca et al, 2014; Stoep et al, 2009); to predict suicidal behavior (Thompson et al, 2009); to recognize patterns in known risk factors for suicide among suicide decedents (Judd et al, 2012; Kim et al, 2003; Logan et al, 2011); to identify psychiatric disorder subtypes that might be more strongly associated with suicidal thoughts or behaviors (Li et al, 2014; Pan et al, 2014); and to explore interactions among suicide risk factors (Pena et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Participants were asked to indicate their level of agreement with each statement on a 3-point scale (0 ¼ not true, 1 ¼ sometimes true and 2 ¼ true). This approach has been used previously by other researchers to assess thoughts of death and suicide (e.g., Vander Stoep, McCauley, Flynn, & Stone, 2009). The composite of the six items represents a single, internally consistent factor (a ¼ .864).…”
Section: Discussionmentioning
confidence: 99%
“…The intensity of being overwhelmed increases the risk for suicidal ideation. In moving through the adolescent stages, thoughts of suicide may become more common (Vander Stoep et al 2009). The challenge of coping may be greater in adolescents with ADHD.…”
mentioning
confidence: 99%